Study of feasibility of laparoscopic inguinal hernia repair in hospital taiping (january 2009 - march 2010) - Hasslinda, Abu Hassan (2010)
The history of inguinal hernia repair (IHR) has gone through many stages of development from the ancient era until today. Inguinal hernia repair is one of the commonest surgical procedure worldwide, irrespective of socioeconomic status or country. Today, with the advancement of laparoscopic surgeries, inguinal hernia has been listed as one of the preferred surgical condition repaired by laparoscopic approach. Nowadays, despite its known complications, advantages and disadvantages, Laparoscopic Inguinal Hernia Repair (LIHR) is widely accepted as the better option of treatment as compared to open approach of inguinal hernia repair (IHR).The purposes of this study is to look for the feasibility of Laparoscopy Inguinal Hernia Repair(LIHR) by Transabdominal preperitoneal (T APP) done in Hospital Taiping. It is al to evaluate the outcome of the procedlire and to look for recurrent. The aim is to improve the services available and to formulate a protocol looking into an opportunity of doing this surgery as a day care basis in future Surgical Department in Hospital Taiping has been offering Laparoscopic Inguinal Hernia Repair since 2004. It was started by a single surgeon , followed by other newcomers with different learning curve. A total of 105 patients have been studied from January 2009 to March 2010. Data related to this study is recorded in Performa and analyze upon completing the time phrame. The male leading the female with a ratio of 16.5:1 and Malays are the majority getting this procedure done with 71 candidates. 59 patients have indirect hernia, 22 patients have direct hernia, 19 patients have both direct and indirect hernia and 5 patients have recurrent hernia. There are 40 cases of right sided hernia, 45 cases of left sided hernia and 20 cases of bilateral inguinal hernia. Majority of the patients seek for treatment after 1 to 3 years of symptoms. All has undergone this elective procedure under general anesthesia.76 patients are in ASAII with the remaining of ASA I. 79% ofthe patients were operated within one to two hours with 74.3% of postoperative ward stay of between two to three days. There were 2 cases of recurrent, which both were indirect type preoperatively. There were 20 cases of wound infection noted during the early review. However, all are managed conservatively and well on the subsequent review. Out of 53 patient documented as working, only 10 patients required medical certificate longer than one week and 52.4% of them took analgesia for less than 48 hours. In summary, the commonest complication of LIHR were wound infection and recurrent. Early recurrent reflect the learning curve. However, analgesia requirement, length of ward stay ,prolongation of medical certificate and absence of other postoperative complications were significant (p value < 0.05) indicating that LIHR is feasible in Taiping Hospital.